The Philosophy of Habermas. - Edgar, Andrew (Taylor and Francis, 2014)
This comprehensive introduction to the thought of Jurgen Habermas covers the full range of his ideas from his early work on student politics to his recent work on communicative action, ethics and law. Andrew Edgar examines Habermas' key texts in chronological order, revealing the developments, shifts and turns in Habermas' thinking as he refines his basic insights and incorporates new sources and ideas. Some of the themes discussed include Habermas' early reshaping of Marxist theory and practice, his characterization of critical theory, his conception of universal pragmatics, his theories of c.